1988
DOI: 10.1007/bf01451528
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of yielding in semicrystalline polymers related to microstructure: Branched polyethylene

Abstract: Abtract:The application of thermodynamics of eutectoid copolymers and a generalized Tabor-rehtion to relationships between mechanical properties (microhardness, yield stress) and microstructure in semicrystalline polymers is considered. The approach is illustrated by resuks on mek-crystallized low density polyethylene, investigated near the yield point at different temperatures. The success of the approach emphasizes that semicrystalline polymers, despke being viscoelastic hetereogeneous systems, give rise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…On the other hand, the presence of iPP crystals does not seem to inhibit the crystallization level of PA and ~PA remains nearly constant. From SAXS results we have seen that L = const, and from calorimetric data (Tm for both PP and PA is constant with composition), we conclude that the crystal thickness, lo, is also constant (the fact that lo = constant simplifies the calculation of the microhardness, as we have shown that Ho is an increasing function of Ic) [8,9]. Then, if we take into account the crystallinity depression measured for the PP component in Equation 4, use for H Pp = 145 MPa and for H Pp = 15 MPa [16], and let H PA = 152 MPa, we are led to curve 2 in Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the presence of iPP crystals does not seem to inhibit the crystallization level of PA and ~PA remains nearly constant. From SAXS results we have seen that L = const, and from calorimetric data (Tm for both PP and PA is constant with composition), we conclude that the crystal thickness, lo, is also constant (the fact that lo = constant simplifies the calculation of the microhardness, as we have shown that Ho is an increasing function of Ic) [8,9]. Then, if we take into account the crystallinity depression measured for the PP component in Equation 4, use for H Pp = 145 MPa and for H Pp = 15 MPa [16], and let H PA = 152 MPa, we are led to curve 2 in Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The experimental microhardness values, Hexp, of the iPP/PA blends, the H values derived from Tabor relation (H ~ 3ay) [7,8], using yield-stress data published elsewhere for these samples [6], and the crystallinity values derived from calorimetry of the iPP and PA components within each blend', ~pp and o%, are collected as function of composition, 4~, in Table II. …”
Section: Microhardness Measurementsmentioning
confidence: 99%
“…During the last two decades it was demonstrated [8][9][10][11][12][13][14][15], that microhardness technique as a nondestructive method, due to its simplicity and high sensitivity, makes it possible to derive relevant information about the structure of polymers. Relationships between microhardness and polymer crystallinity, crystal perfection, chain conformation and other structural parameters have been derived [8,10,15].…”
mentioning
confidence: 99%
“…Relationships between microhardness and polymer crystallinity, crystal perfection, chain conformation and other structural parameters have been derived [8,10,15]. Hardness of polymers can also be correlated with many of their mechanical properties [8][9][10][11], which makes such measurements a fast and convenient method for material characterization. The microhardness technique has also been proved to detect polymorphic phase changes in polymers [12], and especially changes in polymer blends with composition [13,14].…”
mentioning
confidence: 99%
“…To( dp )= Ahf m dT~ A~ (4) where A~ is the specific volume change upon melting for an infinitely thick crystal. iii) From eq 3, T~/dT~= Tm/dTm.…”
mentioning
confidence: 99%